(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
A survey was conducted to study the diversity and population of parasitic Hymenoptera by using Malaise traps, from March 2014 to February 2015 in Chittagong University and Rajshahi University Campus. A total number of 173 genera was identified under 53 subfamilies, 23 families and 7 super families. Among the super families, the highest percentage of species individuals (59%) in Chalcidoidea, and of genera (55%) in Ichneumonoidea were recorded. The Species Richness (SR), H or H’, Hmax, Evenness, Community dominance and Question of similarity indices were applied to determine the diversity and abundance of parasitic hymenoptera. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 63-68